School Human Resource Management (HRM) Strategy Rooted in Culture and Oriented Towards Digital: Responding to Disruption Challenges in an Adaptive and Meaningful Way - Syahfitri, Dinda; Yunera, Syabrina; Syam, Dewi Sumiyarsih; Nellitawati, Nellitawati; Al Kadri, Hanif; Setiawati, Merika (Arfannur: Journal of Islamic Education, 2025)
Digital transformation has fundamentally shifted the paradigm of human resource management (HRM) in the education sector, particularly within school administration, which must now adapt to the dynamics of technological disruption. This article explores a school HRM development strategy rooted in local cultural values and oriented toward digital technology as an adaptive and meaningful response to the demands of the Society 5.0 era. Through a comprehensive literature review and critical analysis, five key pillars are identified: strengthening digital competencies, cultivating a growth mindset, innovating work processes, fostering cross-sector collaboration, and implementing performance management systems based on digital platforms. The study highlights the importance of integrating local wisdom in shaping resilient and collaborative human resources while accelerating inclusive and context-sensitive technology adoption. The practical implications of this research offer strategic directions and policy recommendations for educational institutions and stakeholders aiming to build adaptive, innovative, and sustainable school governance in the face of ongoing disruption.